Hydrothermal catalytic processing of waste cooking oil for hydrogen-rich syngas production. (23rd February 2019) - Nanda, Sonil; Rana, Rachita; Hunter, Howard N.; Fang, Zhen; Dalai, Ajay K.; Kozinski, Janusz A.
Graphical abstract: Highlights: Waste cooking oil was gasified in supercritical water for hydrogen production. Effects of temperature, feed concentration, reaction time and catalysts were studied. High H2 yields were obtained at 675 °C and 60 min with 25 wt% of waste cooking oil. Ru/Al2 O3 maximized H2 yields due to decarboxylation, decarbonylation and water-gas shift reaction. Glycerol, acetic acid and propionic acid were obtained as the main degradation products of cooking oil. Abstract: Substantial amounts of waste cooking oil are obtained worldwide from household and catering enterprises because of deep-frying and other cooking activities. Supercritical water gasification is considered as an aqueous phase reforming process to produce hydrogen enriched syngas from biomass and other organic wastes. In this study, waste cooking oil was gasified at variable temperatures (375–675 °C), feed concentration (25–40 wt%) and reaction time (15–60 min) to investigate their effects on syngas yield and composition. Maximum yields of hydrogen (5.16 mol/kg) and total gases (10.5 mol/kg) were obtained at optimal temperature, feed concentration and reaction time of 675 °C, 25 wt% and 60 min, respectively. At 5 wt% loading, Ru/Al2 O3 enhanced hydrogen yield (10.16 mol/kg) through water-gas shift reaction, whereas Ni/Si-Al2 O3 improved methane yield (8.15 mol/kg) via methanation reaction. The trend of hydrogen production from catalytic supercritical water gasification of waste cooking oil at 675 °C, 25 wt% and 60 min decreased as Ru/Al2 O3  > Ni/Si-Al2 O3  > K2 CO3  > Na2 CO3 . The results indicate the recycling potential of waste cooking oil for hydrogen production through hydrothermal gasification.